Peran Kampus Mengajar V dalam Adaptasi Tekonolgi Bagi Guru di SDN 3 Petuk Katimpun - Tarita Aprilani Sitinjak (FKIP Universitas Palangka Raya, 2024)
Technology adaptive in targeted schools are one of the teaching campuss programs for interesting learning, increasing study motivation and study result of students. However in SDN 3 petuk Katimpun the teacher still using a convention learning model. The research aim is to understand the role of the teaching campuss in technology adaption for teacher in SDN 3 Petuk Katimpun. The reseach was used a descriptive qualitative method and was held in a month. Data collected by doing observation, interview and documentation. The result show that after the mentoring about adaptive technology was held by the researcher and member of the teaching campuss, the teacher was able to produce an interesting media learning and the teaching campuss has important role in order to increase the capability of teacher’s technology adaptation